2011
DOI: 10.1111/j.1600-0897.2011.01069.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Properties of Mesenchymal Stem Cells: Cytokines and Factors

Abstract: Mesenchymal stem cells (MSCs) are defined as undifferentiated cells that are capable of self renewal and differentiation into several cell types such as chondrocyte, adipocyte, osteocyte, myocyte, hepatocyte, and neuron-like cells. MSC can be isolated from bone marrow, umbilical cord blood, adipose tissue, placenta, periosteum, trabecular bone, synovium, skeletal muscle, and deciduous teeth. Immunomodulatory of MSCs is one of the important issues nowadays, because this aspect can be clinically applied for graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
163
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(176 citation statements)
references
References 134 publications
(211 reference statements)
3
163
0
3
Order By: Relevance
“…The results also indicate that the suppression of MSCs is associated with or mediated by PGE2, which has been previously observed for UCMSCs (Kim et al, 2015;Yu et al, 2014). However, many published publications have also suggested the role of other factors (TGFbeta, HGF, PGE 2 , NO, and IDO) in immune modulation by MSCs (Ma et al, 2014;Soleymaninejadian et al, 2012;Zhao et al, 2016).…”
Section: Discussionmentioning
confidence: 45%
“…The results also indicate that the suppression of MSCs is associated with or mediated by PGE2, which has been previously observed for UCMSCs (Kim et al, 2015;Yu et al, 2014). However, many published publications have also suggested the role of other factors (TGFbeta, HGF, PGE 2 , NO, and IDO) in immune modulation by MSCs (Ma et al, 2014;Soleymaninejadian et al, 2012;Zhao et al, 2016).…”
Section: Discussionmentioning
confidence: 45%
“…It is noteworthy that despite previously published data suggesting the importance of IL-10 in MSC-mediated immunosuppression [40][41][42], to our knowledge, no one has yet demonstrated that the putative effects of IL-10 could be reversed by blocking the IL-10 pathway. Such a discrepancy may not only be explained by the redundancy of MSC-induced inhibitory mechanisms [43][44][45], but also by the simple fact that while IL-10 + IFNg + T-cells are being generated during the first stimulation by the presence of MSCs, their accumulation occurs too late to have any effect.…”
Section: Cd25mentioning
confidence: 55%
“…Regarding the mechanism of action of MSCs, as stated earlier, researchers are suggesting that, the therapeutic benefits of MSCs in RORM might be mediated by their paracrine effects with or without homing to the injury site, rather than their differentiation properties replacing the damaged cells [55,70,71,195,196].…”
Section: Chapter 7 Discussionmentioning
confidence: 99%